Ability, parental background and education policy: Empirical evidence from a social experiment - Costas Meghir; Mårten Palme (Institute for Fiscal Studies (IFS), 2003)
Following the great expansion of secondary education in the United States between 1910 and 1940, Sweden was one of the first Western European countries to attempt such an expansion by increasing the years of compulsory schooling and and improving access to academic type education by abolishing early selection. The reform was preceded by a large-scale area based social experiment where 25% of the country's municipalities were assigned to the reform. We use this assignment, together with rich individual data to evaluate this major educational intervention. Our key findings are that this reform increased the educational attainment of individuals with unskilled fathers. In addition it caused significant and large increases in the earnings of those with unskilled fathers and above median ability.
Keywords: 330; Bildungsreform; Bildungspolitik; Allgemeinbildende Schule; Bildungsertrag; Schweden